HBV capsid assembly modulators differentially modulate the assembly of wild-type and drug-resistant core protein chimeric nucleocapsids and empty capsids. - Hui Liu; Hemraj Rimal; Jun Lyu; Liangxian Shen; Qiong Zhao; Jinhong Chang; Ju-Tao Guo (PLoS Pathogens)
Multiple capsid assembly modulators (CAMs) are in clinical development for the treatment of chronic hepatitis B. The emergence of CAM-resistant HBV has resulted in the failure of CAM antiviral therapy in recent clinical trials. Because wild-type (WT) and CAM-resistant core protein (Cp) can co-assemble to form chimeric capsids, it is important to understand how CAMs modulate the assembly and disassembly of chimeric capsids and how CAM-resistant HBV variants emerge under CAM antiviral therapy. In addressing these questions, we found that in human hepatoma cells co-transfected with a serial molar ratio of WT and mutant HBV replicons expressing CAM-resistant Cp, expression of as few as 10% WT Cp conferred inhibition of nucleocapsid assembly by CAMs. However, 50% Cp with T33N substitution conferred complete resistance to the assembly of chimeric empty capsids induced by AB-506 but remained sensitive to GLS4, as determined in an in vitro capsid assembly assay and in transfected hepatoma cells. Moreover, the existence of approximately 50% WT Cp in chimeric nucleocapsids is required for CAMs to induce the disassembly of mature nucleocapsids and inhibit the infection of hepatocytes by HBV virions with chimeric nucleocapsids. Our results thus suggest that although disruption of nucleocapsid assembly requires only small numbers of CAM binding pockets at Cp dimer-dimer interfaces to be engaged, induction of mature nucleocapsid disassembly requires much larger numbers of CAM binding pockets to be occupied. The strong WT Cp dominance in CAM suppression of nucleocapsid assembly may slow down the emergence of CAM-resistant HBV variants under CAM therapy.